Correlation of Platelet Receptor Expression in Glanzmann Thrombasthenia with Clinical Presentation and Haematological Parameters - Cheema, Ahmad; Bozdar, Manzar; Malik, Hamid Saeed; Hussain, Muhammad; Mahmood, Rafia; Khan, Aysha; Khurshid, Ayesha; Shafaat, Syeda Samia (Pakistan Armed Forces Medical Journal, 2026)
Objective: To correlate platelet receptor expression with clinico-haematological parameters in patients of Glanzmann Thrombasthenia.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Pathology/National University of Medical Sciences (NUMS), Rawalpindi Pakistan, from Jan 2023 to Jan 2024.Methodology: Patients of Glanzmann thrombasthenia (GT) diagnosed by light transmission aggregometry were evaluated for the expression of CD 41 and CD 61 on platelet surface by flow cytometry. Data was assessed using BD FACS DIVA software. The correlation between the haematological parameters, clinical presentation based on bleeding assessment tool (BAT), and GT subtypes based on flow cytometric analysis was assessed.Results: A total of 73 patients of GT were included in this study with mean age of 5.24±1.86 years. There were 31 males (42.47%) and 42 females (63.01%). Out of these patients, 46(63.01%) were classified as Type I (CD41/CD61 was absent or less than 5%). 21(28.77%), as Type II (5-25% CD41/CD61) and 06(8.22%) as Type III (CD41/CD61 greater than 25%). BAT score showed a significant, strong and negative correlation with platelet receptor expression (r=0.607, p